Mandapa (pillared hall) of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the pillar in the central chatuski of the mandapa (pillared hall) of the Neelkanth Mahadev Temple. This pillar typology is similar to the pillars of the mukhamandapa (front porch). Octagonal shafts with foliage ornamentation, maladharas sculptures on all sides of the shafts are characteristics of the pillar.